Football development strategies for Sarawak Football Association / Muhamad Afzal Jahangir - Jahangir, Muhamad Afzal; Hashim, Nidzam Adzhar (2017)
This research examines the performance of Sarawak Football Association (FA) in the football competition in Malaysia which is the Malaysia Super League, Malaysia Premier League, Malaysia FA cup and Malaysia Cup and Malaysia Sumbangsih Cup. Sarawak FA had a good performance in their past but lately, their performance are not as good as the past. This research will be conducting in Kuching, Sarawak. This study use quantitative method to analyze data. The data collected from 100 respondents by distribution of questionnaires. The researcher use Descriptive Analysis for quantitative method. This research argues about the suitable strategies that Sarawak FA needed to improve their football development performance.